Detection of Hepatitis B Core Antigen using a Fusion Bacteriophage - Hasmoni, Siti Salwa (2005)
Due to the many reported cases of hepatitis B disease around the world, a keen interest among researches has aroused on the cause of the disease, hepatitis B virus (HBV). One of the serological markers for HBV is hepatitis B core antigen (HBcAg) that is a marker of the infectious material and it is the most accurate index of the viral replication. The importance of the HBcAg especially when considering the close relationship with the viral DNA load has created revolutionary studies on the HBcAg ever since. The HBV nucleocapsid or HBcAg is extremely immunogenic during infection and after immunization. A fusion bacteriophage that interacts with HBcAg has been isolated from a phage display peptide library. The phage interacts tightly to HBcAg and thus has the potential to be further developed as a diagnostic reagent. In this study, two immunoassays have been developed using the fusion bacteriophage to detect HBcAg. Phage-ELISA and phage-dot blot assay could detect not only purified HBcAg but also HBcAg in serum samples. As low as 10 ng of HBcAg can be significantly detected by 1 012 pfulml of fusion phage when the reading at 405 nm was measured (hO= 5 0.4). Using the fusion bacteriophage, these newly developed immunoassays provide an easier and cheaper option for detecting HBcAg. The sensitivity of these immunoassays demonstrates the potential and perhaps vast future uses to detect HBcAg. The fusion phage is also capable of purifying the HBcAg due to its capability to precipitate HBcAg.